Magnetic beads as versatile tools for electrochemical DNA and protein biosensing - Palecek, Emil; Fojta, Miroslav (Talanta, 2007)
Magnetic beads (MBs) are versatile tools in the separation of nucleic acids, proteins and other biomacromolecules, their complexes and cells. In this article recent application of MBs in electrochemical biosensing and particularly in the development of DNA hybridization sensors is reviewed. In these sensors MBs serve not only for separation but also as a platform for optimized DNA hybridization. A hybridization event is detected separately at another surface, which is an electrode. The detection is based either on the intrinsic DNA electroactivity or on various kinds of DNA labeling, including chemical modification, enzyme tags, nanoparticles, electroactive beads, etc., greatly amplifying the signals measured. In addition to DNA hybridization, other kinds of biosensing in combination with MBs, such as DNA-protein interactions, are reviewed.
Keywords: Electrochemistry; nanostruktury; Magnetics; Proteins; biosenzitivní techniky; Biosensing Techniques; Humans; Nanostructures; Microspheres; mikrosféry; elektrochemie; magnetismus; DNA; lidé; proteiny